Abbreviations for Device Names: A Proposed Methodology With Specific Examples. Issue 4 (22nd February 2013) - Alam, Murad; Dover, Jeffrey S.; ,; ,; Alam, Murad; Goldman, Mitchel P.; Kaminer, Michael S.; Orringer, Jeffrey; Waldorf, Heidi; Alam, Murad; Avram, Mathew; Cohen, Joel L.; et al.
<x xml:space="preserve">Abstract</x> Background Many devices used in dermatology lack generic names. If investigators use commercial device names, they risk the appearance of bias. Alternatively, reliance on ad‐hoc names and abbreviations may confuse readers who do not recognize these. Objective To develop a system for assigning abbreviations to denote devices commonly used in dermatology. Secondarily, to use this system to create abbreviations for FDA‐approved neurotoxins and prepackaged injectable soft‐tissue augmentation materials. Methods The American Society for Dermatologic Surgery convened a Lexicon Task Force in March 2012. One charge of this Task Force was to develop criteria for assigning abbreviations to medical devices. A modified consensus process was used. Results Abbreviations to denote devices were to be: based on a standardized approach; transparent to the casual reader; markedly brief; and in all cases, different than the commercial names. Three‐letter all caps abbreviations, some with subscripts, were assigned to denote each of the approved neurotoxins and fillers. Conclusion A common system of abbreviations for medical devices in dermatology may avoid the appearance of bias while ensuring effective communication. The proposed system may be expanded to name other devices, and the ensuing abbreviations may be suitable for journal articles, continuing medical education lectures, or other academic or clinical purposes.